2009
DOI: 10.1104/pp.109.148585
|View full text |Cite
|
Sign up to set email alerts
|

Generation of Backbone-Free, Low Transgene Copy Plants by Launching T-DNA from theAgrobacteriumChromosome

Abstract: In both applied and basic research, Agrobacterium-mediated transformation is commonly used to introduce genes into plants. We investigated the effect of three Agrobacterium tumefaciens strains and five transferred (T)-DNA origins of replication on transformation frequency, transgene copy number, and the frequency of integration of non-T-DNA portions of the T-DNA-containing vector (backbone) into the genome of Arabidopsis (Arabidopsis thaliana) and maize (Zea mays). Launching T-DNA from the picA locus of the Ag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
54
1

Year Published

2012
2012
2019
2019

Publication Types

Select...
4
3
2

Relationship

2
7

Authors

Journals

citations
Cited by 77 publications
(57 citation statements)
references
References 48 publications
(60 reference statements)
2
54
1
Order By: Relevance
“…A recent study has shown that launching T-DNA from the plant-inducible picA locus in the A . tumefaciens chromosome was found to reduce transgene copy number and almost eliminate the presence of T-DNA backbone sequences in Arabidopsis and maize (Oltmanns et al 2010 ) . Such a strategy may enable transgenic sugarcane plants produced by Agrobacterium -mediated transformation to exhibit higher levels of transgene expression but also free of residual antibiotic resistance genes and backbone sequences.…”
Section: Availability Of New Transformation Vectorsmentioning
confidence: 99%
“…A recent study has shown that launching T-DNA from the plant-inducible picA locus in the A . tumefaciens chromosome was found to reduce transgene copy number and almost eliminate the presence of T-DNA backbone sequences in Arabidopsis and maize (Oltmanns et al 2010 ) . Such a strategy may enable transgenic sugarcane plants produced by Agrobacterium -mediated transformation to exhibit higher levels of transgene expression but also free of residual antibiotic resistance genes and backbone sequences.…”
Section: Availability Of New Transformation Vectorsmentioning
confidence: 99%
“…The Agrobacteriummediated method also generates transgenic events that carry DNA fragments outside the T-DNA region (vector backbones) (Shou et al, 2004), which is an undesired effect. To prevent extra DNA segments from being inserted into the genome, some researchers used purified DNA fragments that carry only the cassette with the gene of interest for bombardment (Breitler et al, 2002;Loc et al, 2002), whereas others devised multiple T-DNA borders (Kuraya et al, 2004) or launched T-DNA from the Agrobacterium chromosome (Oltmanns et al, 2010) frequency. In the future, both methods will probably be needed to maximize the genetic transformation of plants.…”
Section: Resultsmentioning
confidence: 99%
“…Transgene integration in the plant genome is a complex process. Generally, Agrobacterium-mediated genetic transformation produces transgenic lines with a relatively low (1-3) transgene copy number (Kohli et al 2003;Olhoft et al 2004;Oltamanns et al 2010;Fladung et al 2013). Particle bombardment transformation method, on the other hand, typically integrates on average higher (1-10 or even up to 100) transgene copy number and complex integration in the genome (Svitashev and Somers 2001;Makarevitch et al 2003;Kohli et al 2003).…”
Section: Gene Targeting and Genome Editingmentioning
confidence: 98%